Overcome by modernity : history, culture, and community in interwar Japan - Harootunian, Harry D., 1929- (Princeton University Press, 2000)
In the decades between the two World Wars, Japan made a dramatic entry into the modern age, expanding its capital industries and urbanizing so quickly as to rival many long-standing Western industrial societies. How the Japanese made sense of the sudden transformation and the subsequent rise of mass culture is the focus of Harry Harootunian's fascinating inquiry into the problems of modernity. Here he examines the work of a generation of Japanese intellectuals who, like their European counterparts, saw modernity as a spectacle of ceaseless change that uprooted the dominant historical cultur.